2017
DOI: 10.7759/cureus.1051
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Volunteering at a Student-Run Free Healthcare Clinic on Medical Students' Self-Efficacy, Comfortableness, Attitude, and Interest in Working with the Underserved Population and Interest in Primary Care

Abstract: IntroductionThe number of primary care physicians in the United States continues to lag behind the number of uninsured people. There has been a growing demand for medical students to improve their self-efficacy, comfortableness, attitude, and interest in working with the underserved and in primary care. This study aims to discern whether volunteering at a student-run, free healthcare clinic has a positive impact on these five variables of interest or not.MethodsA 95-item survey was distributed through Qualtric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Further, understanding medical student experience at SRFCs is important in encouraging students to go on to work with vulnerable populations as physicians. Similar to other studies evaluating student experience, our findings demonstrate that volunteering at SRFCs does not impact student desire to work in primary care or underserved settings in the future [16,17]. Medical students choose to volunteer at SHAWCO in addition to their core curricular activities and are not required to participate.…”
Section: Discussionsupporting
confidence: 78%
“…Further, understanding medical student experience at SRFCs is important in encouraging students to go on to work with vulnerable populations as physicians. Similar to other studies evaluating student experience, our findings demonstrate that volunteering at SRFCs does not impact student desire to work in primary care or underserved settings in the future [16,17]. Medical students choose to volunteer at SHAWCO in addition to their core curricular activities and are not required to participate.…”
Section: Discussionsupporting
confidence: 78%
“…A total of 24 articles assessed the effectiveness of educational interventions [ 20 , 21 , 31 , 36 , 37 , 39 , 41 , 46 48 , 50 , 51 , 53 , 55 , 58 , 60 , 61 , 65 , 69 , 70 , 72 , 75 77 ]. Twenty were US studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen were controlled-group studies [ 20 , 21 , 36 , 37 , 46 , 47 , 49 , 50 , 60 , 61 , 59 , 70 , 72 ], among which two were randomized [ 46 , 60 ]. Five main types of educational interventions were evaluated: global curriculum dedicated to social accountability [ 20 , 21 , 36 , 46 , 47 , 48 , 50 , 51 , 53 , 60 , 61 , 72 , 77 ]; experiential community-based learning [ 37 , 41 , 70 ]; volunteering in student-run free clinics [ 55 , 58 , 69 , 76 ], traditional didactic learning ,, [ 31 , 39 , 65 ] and online curriculum [ 75 ]. Experiential community-based learning and global curricula showed the greatest positive impact on MS-ATU, whereas volunteering in student-run free clinics and traditional learning showed inconsistent results.…”
Section: Resultsmentioning
confidence: 99%
“…Providing a positive educational environment where students can interact with patients may help them develop more positive attitudes toward patients with special needs. [1011] A study conducted by Dao et al . [12] found that more the education, dentists had received about providing care for patients with special needs, the better their attitudes and the more likely they were to provide services for these patients.…”
Section: Introductionmentioning
confidence: 99%